A Critical Survey of Comparative Studies conducted about Rūmī and Mathnawi - Khoshbaf Torghabeh, M.; Ghavam. A, Taghavi. M, (Opción, 2019)
This paper aims to investigate the comparative studies done on Rūmī in the past decade and elaborate on their strengths and weaknesses with use of time-based, journals-status and content-based and journals’ specialty sampling as methodology. The findings showed that most of the papers suffered from serious drawbacks such as inadequate coverage and familiarity with subject matter, overgeneralization, superficial analysis and hasty conclusions. Some writers' traditional and subjective approach to the issue was much highlighted in certain journals, whereas few enjoyed scientific precision. Other defects that can be listed include: lack of systematic methodology, false inferences, inappropriate references, selection of insignificant.